LEAF LITTER DECOMPOSITION PATTERN OF TREES - BHALAWE, SHAILENDRA; D. NAYAK; M. U. KUKADIA; GAYAKVAD, PARESH (The Bioscan, 2013)
Experiment was conducted to study the leaf litter decomposition and nutrient release pattern of seven multipurpose trees Tectona grandis, Eucalyptus tereticornis, Dendrocalamus strictus, Terminalia bellirica, Cassia fistula, Casuarina equisetifolia, Terminalia arjuna were evaluated using litter bag technique. Results showed that, weight loss and decay rate higher in T. grandis (25.92%) followed by D. strictus (23.08%), T. arjuna (22.12%) and least in C.equisetifolia (20.51%). Litter nutrient (N, P, K), days elapsed and climatic factor (rainfall, temperature and humidity) of the study site were found to influence the rate of decomposition and significantly correlated to each other. Nutrient release pattern found higher in T. grandis and gradually followed by D. strictus > T. arjuna > T. bellirica > C. fistula > E. tereticornis > C. equisetifolia. Initial days of leaf litter decomposition and nutrient release faster and after that gradually slow down due to the influence of climatic parameter. Hence, rainfall, humidity, temperature and microclimate seem to be control the decomposition more effectively and strongly than any other combination of climatic variables.